Design, recruitment, and baseline characteristics of the LENS trial - The LENS Collaborative Group (Wiley, 2024)
Background: Findings from cardiovascular outcome trials suggest that treatment with fenofibrate may reduce the progression of diabetic retinopathy. However, no dedicated large-scale randomised trials have yet investigated this hypothesis. Methods: LENS is a streamlined randomised double-masked placebo-controlled trial, based in Scotland, assessing whether treatment with fenofibrate (145 mg tablet daily or, in the context of impaired renal function, on alternate days) in people with early retinopathy reduces progression to referable diabetic retinopathy (defined in NHS Scotland's Diabetic Eye Screening grading scheme as referable background or proliferative retinopathy, or referable maculopathy in either eye) or treatment with retinal laser, intravitreal injections or vitrectomy. Adults with diabetes mellitus and non-referable retinopathy (mild background retinopathy in both eyes or observable background retinopathy in one/both eyes at the most recent NHS retinal screening assessment; or observable maculopathy in one/both eyes in the previous 3 years) were eligible. Potential participants were identified from routinely collected healthcare data and followed up using regular contact from the research team and linkage to national electronic morbidity, mortality, biochemistry and retinal screening records. Study treatment was mailed to participants. Results: Between 18 September 2018 and 27 July 2021, 1151 participants were randomised. Their mean age was 61 (SD 12) years, 312 (27%) were female and 305 (26%) had type 1 diabetes. 96% had bilateral mild background retinopathy and 10% had observable maculopathy. Conclusions: LENS will provide a robust evaluation of the efficacy of treating people at risk of progression of diabetic retinopathy with fenofibrate. Results are anticipated in mid-2024. Trial Registrations: NCT03439345; ISRCTN15073006; EuDRACT 2016–002656-24.